Molar Hypomineralisation: A Call to Arms for Enamel Researchers - Hubbard, Michael J.; Mangum, Jonathan E.; Perez, Vidal A.; Nervo, Garry J.; Hall, Roger K. (Frontiers in Physiology, 2017)
Developmental dental defects (DDDs, hereafter 'D3s') hold significance for scientists and practitioners from both medicine and dentistry. Although attention has classically dwelt on three other D3s (amelogenesis imperfecta, dental fluorosis and enamel hypoplasia), dental interest has recently swung towards Molar Hypomineralisation (MH), a prevalent condition characterised by well-delineated ('demarcated') opacities in enamel. MH imposes a significant burden on global health and has potential to become medically preventable, being linked to infantile illness. Yet even in medico-dental research communities there is only narrow awareness of this childhood problem and its link to tooth decay, and of allied research opportunities. Major knowledge gaps exist at population, case and tooth levels and salient information from enamel researchers has sometimes been omitted from clinically-oriented conclusions. From our perspective, a cross-sector translational approach is required to address these complex inadequacies effectively, with the ultimate aim of prevention. Drawing on experience with a translational research network spanning Australia and New Zealand (The D3 Group; www.thed3group.org), we firstly depict MH as a silent public health problem that is generally more concerning than the three classical D3s. Second, we argue that diverse research inputs are needed to undertake a multi-faceted attack on this problem, and outline demarcated opacities as the central research target. Third, we suggest that, given past victories studying other dental conditions, enamel researchers stand to make crucial contributions to the understanding and prevention of MH. Finally, to focus geographically diverse research interests onto this nascent field, further internationalisation of The D3 Group is warranted.